Konsep Idealisasi Penegakan Hukum Pajak dengan Eliminasi Administrative Penal Law terhadap Pelanggaran Pajak di Indonesia - Sahal Hanafi (Universitas Sains dan Teknologi Komputer, 2023)
The position of tax law also called as public law because it cannot be separated from the administrative law section. Through the mandate of the constitution, the state is authorized to collect taxes and regulate tax law enforcement. The legality of the tax so that the existence of the tax arises because it has a function as the receipt of state revenue funds. If the coherence is consistent with the tax function, then the law enforcement will be maximally in line with the tax function. Otherwise, the fact shows that in tax law enforcement with criminal sanctions there are still counter-productive to its function, so that it is necessary to idealize a more effective and efficient tax law enforcement so that it is in line with the intention of the tax function. By using normative juridical research methods and conceptual approach, comparative approach. This research can provide an overview of the problem of the implementation of criminal sanctions in the constellation of tax law that is less effective and efficient. On the contestation of criminal sanctions and administrative sanctions in tax law enforcement, a consensus can be taken that administrative sanctions are more dominant because of the orientation of financial coercion.